Prevalence and associated features of self-reported freezing of gait in Parkinson disease: The DEEP FOG study. Issue 6 (June 2015) - Amboni, M.; Stocchi, F.; Abbruzzese, G.; Morgante, L.; Onofrj, M.; Ruggieri, S.; Tinazzi, M.; Zappia, M.; Attar, M.; Colombo, D.; Simoni, L.; Ori, A.; et al.
Abstract: Freezing of Gait (FOG) is a common and disabling symptom in patients with Parkinson disease (PD). The relationship between FOG and dopaminergic medication is complex. The aim of the present study was to estimate the prevalence of self-reported FOG, its associated clinical features, and its relationship with wearing-off in a wide PD population. This is an observational multicenter study of 634 consecutive non-demented PD patients. Patients were identified either as freezers or non-freezers based on item-3 of the Freezing of Gait-Questionnaire. FOG was then classified as on, off and onoff freezing based on its relationship with wearing-off. Patients were assessed with Unified Parkinson's Disease Rating Scale, Hoehn and Yahr scale, 8-item Parkinson's disease Questionnaire, Mini-Mental State Examination. Data from 593 patients were analyzed, 325 (54.3%) were freezers of whom 200 (61.6%) experienced FOG only during off state (off-freezers), 6 (1.8%) only during on state and 119 (36.6%) either in on and off states or independently of dopaminergic response-related symptoms (onoff-freezers). Overall, freezers vs non-freezers had longer disease duration, more advanced disease and greater disability. Moreover, freezers more frequently reported wearing-off and experienced worse quality of life. Onoff-freezers vs off-freezers were older, more severely disabled, less likely to experience wearing-off, treated with lower levodopa equivalent daily dose and with poorer cognitive performance. Self-reported FOG is mainly recognizable in advanced PD and is associated with more disability and worse quality of life. Onoff-FOG may represent the result of under-treatment or rather interpretable as a distinct clinical entity.